The Determinant of Unintended Pregnancies Among Women of Pakistan - Fiza, Hina; Kausar, Syeda Tasneem; Parveen, Kousar; Batool, Sajida (Biological and Clinical Sciences Research Journal, 2025)
Unintended pregnancies remain a major public health concern worldwide, particularly in low and middle-income countries. In Pakistan, socioeconomic constraints, limited access to reproductive health services, unmet contraceptive needs, and restricted spousal communication continue to influence reproductive outcomes. This study aimed to identify the key sociodemographic and reproductive determinants associated with unintended pregnancies among married women attending a tertiary care hospital in Lahore. Methods: A descriptive cross-sectional study was conducted among 171 married women of reproductive age visiting the gynecology outpatient department. Participants were selected through convenience sampling. Data were collected using a structured, validated questionnaire that assessed sociodemographic variables, contraceptive use, communication patterns, reproductive history, and access to communication tools. Statistical analysis was performed using SPSS version 26. Descriptive statistics summarized participant characteristics, while chi-square tests determined associations between independent variables and unintended pregnancy. A p-value below 0.05 was considered statistically significant. Results: The majority of participants were aged 31–35 years (42.1%), resided in urban areas (67.3%), and had secondary education (51.5%). More than half (55.6 percent) had never used contraception, and 38.6 percent had never discussed family planning with their spouses. Unintended pregnancies were significantly associated with non-use of contraception (71.6 percent vs 42.1 percent, p<0.001), lack of spousal communication (69.7 percent vs 39.1 percent, p<0.001), short birth intervals below 12 months (p=0.003), younger age (p=0.042), low educational attainment (p=0.038), limited access to communication tools (p=0.050), and history of miscarriage (p=0.021). Residence, gravidity, parity, and family size did not show significant associations. Conclusion: This study highlights the multifactorial nature of unintended pregnancies in Pakistan, emphasizing the role of contraceptive uptake, effective partner communication, education, and birth spacing. Addressing these determinants through culturally sensitive counseling, enhanced family planning services, and community-based awareness programs could reduce unintended pregnancies and improve reproductive health outcomes among married women.